MAKNA INTERAKSI SOSIAL DI DALAM KELAS DI SMP N 22 PADAMG PADA PEMBELAJARAN IPS - Rahmi, Rizka Fitri (Pendidikan Sosiologi, 2014)
Inteaching learning of social depertment knowledge of interaction see the interactions, these conditionshave an impact on the relationship between students and teachers. The problems that is see between teachers andstudents in learning the English language less interaction goes well, it evident in the classroom when the teacher inthe classroom. It can be seen, teachers rareky made it evident, teachers do not care to students who commit offensessuch as talking with pair teaching learning of social knowledge at SMP N 22 Padang.The theory was used by theresearcher is the symbolic interactional theory. The design of the research is a qualitative approacg and descriptive.In this study, the researcher used purposive sampling to take time informan. The informants in this study was asocial studies teacher and eighth grade students. The data used in this study are primary and secondary data. The unitaf analysis is the group with the analysis of the data using content analysis. The results of this study are notemeaning of social interaction betweet teachers and students in learning social studies. Social interaction can be seein preliminary, whi ist past teaching and post teaching activities. Meaning of interaction for teachers includes 1. Theteacher took students attendance list t, by taking studentsâ attendance list, the teachers students name ,and studentsfeel anthusias whe teacher whe students vary in learning always remember how the teacher which could make themunderstand the material being taught, 3. In closing the meaning that see with the teacher giving the lesson conclusionavery teacher can know in this way the students will be strengthen the understanding of the material.